2018
DOI: 10.7150/jca.24557
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Toxicity of Lobaplatin-contained Chemotherapy in Extensive-stage Small-cell Lung Cancer

Abstract: To assess the efficacy and toxicity of Lobaplatin (LBP) -contained chemotherapy on extensive stage small-cell lung cancer (ES-SCLC), we conducted a prospective, single-arm, and multicenter Phase IV clinical trial on Lobaplatin (ChiCTR-ONC-13003471), and used the patient clinical data obtained from our cancer center to perform the analysis. Previously untreated patients with ES-SCLC were given LBP intravenously (IV) at 30 mg/m2 on day 1 and etoposide IV at 100 mg/m2 on day 1, 2, and 3. The treatment was cycled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Combination chemotherapy with irinotecan and cisplatin for SCLC leads to equal or better survival than etoposide and cisplatin, with median survival of 9.3–12.8 months . A phase III study of EL in ES‐SCLC patients and other studies on the EL regimen reported median PFS and DCR of 4.7–6.5 months and 69.5–90.4%, respectively, in first‐line treatment . Our results are consistent with the findings of these studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Combination chemotherapy with irinotecan and cisplatin for SCLC leads to equal or better survival than etoposide and cisplatin, with median survival of 9.3–12.8 months . A phase III study of EL in ES‐SCLC patients and other studies on the EL regimen reported median PFS and DCR of 4.7–6.5 months and 69.5–90.4%, respectively, in first‐line treatment . Our results are consistent with the findings of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…21,22 A phase III study of EL in ES-SCLC patients and other studies on the EL regimen reported median PFS and DCR of 4.7-6.5 months and 69.5-90.4%, respectively, in firstline treatment. [23][24][25][26] Our results are consistent with the findings of these studies. The median PFS and DCR in our study cohort were 6.8 months and 90% in all patients (limited vs. extensive stage: 9.6 vs. 5.9 months, 100% vs. 84%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, while nedaplatin led to less gastrointestinal toxicities, nephrotoxicity, ototoxicity, and neurotoxicity compared with cisplatin, more hematologic toxicities such as grade 3/4 neutropenia and thrombocytopenia were seen in nedaplatin-treated patients (7,8). Lobaplatin is another platinum compound showing anti-tumor activity in multiple solid tumors such as breast cancer, small-cell lung cancer, and hepatocellular carcinoma (10)(11)(12). Lobaplatinbased induction chemotherapy followed by lobaplatin-radiotherapy showed comparable survival outcomes but less acute toxicities than cisplatin-based concurrent chemoradiotherapy in locally advanced nasopharyngeal carcinoma and might be a promising alternative to cisplatin-based treatment (13).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Compared with other traditional platinum drugs, such as cisplatin and carboplatin, lobaplatin, a third-generation alkylating antineoplastic drug, has the advantages of high solubility in water, good stability, wide anticancer spectrum and high antitumor activity. It has been investigated in patients with advanced solid tumors, including gastric cancer, 8,9 colorectal cancer, 10,11 hepatocellular carcinoma, 12,13 small-cell lung cancer, 14 and appendicular osteosarcoma. 15 However, the safety and efficacy of lobaplatin, especially when used in combination with HIPEC for the purposes of treating peritoneal appendiceal and colorectal cancer metastases, remain unclear.…”
Section: Introductionmentioning
confidence: 99%